Penerapan Fungsi-Fungsi Manajemen Pada Proses Penerimaan Bahan Baku Ikan Lemuru di PT. Sarana Tani Pratama Jembrana-Bali - Sartini Sartini; Budiman Haruna; Karma Karma (Jurnal bintang manajemen, 2025)
The process of receiving raw materials is the initial activity of a production process, the quality of raw materials can affect the quality of the final product, quality control must be carried out so that the raw materials to be used comply with industry specifications to produce quality products. For example, the raw material for frozen fish at PT Sarana Tani Pratama Jembrana, Bali, whether local frozen fish or imported frozen fish, is thawed using the water immersion method. The difference in the Thawing process or melting process between local frozen fish and imported frozen fish is the thawing time, where local frozen fish takes ±2 hours for the Thawing process while imported frozen fish only takes ±30 minutes for the melting process. The difference in thawing time is caused by local frozen fish being sent by the supplier frozen per block, which consists of several fish in one block. Meanwhile, imported frozen fish is sent by the supplier frozen per fish.This research aims to determine the Application of Management Functions in the Process of receiving raw materials at PT.Sarana Tani Pratama Jembrana-Bali. The types of data used are primary data and secondary data with data collection techniques including observation, interviews and literature study. The data analysis used is descriptive/qualitative data analysis.